Fenomena Sosiologis Metamorphosis Petani: ke Arah Keberpihakan pada Masyarakat Petani di Pedesaan yang Terpinggirkan Terkait Konsep Ekonomi Kerakyatan - Roosganda Elizabeth (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2007)
EnglishThe adoption of modernization paradigm which majoring efficiency principle in agricultural development has caused the change in rural peasant social structure. The changes are especially related to farm land ownership creating the substratum of peasant, i.e., the upper and lower level of peasant. All peasant definitions are equal by its diametric and equip by each other, so that it needs a study in relation to its pattern change, interaction, and institution that historically experienced by the peasant society. The influencing development factors affecting peasant daily life should refer to the potential and the empowerment of the society. This is very important in order to adapt and sustain the development without losing the norms, values, and souls of indigenous knowledge. Ekonomi kerakyatan (people’s economy) concept represents the economic idea trying to formulate the interpretation base and the development aspiration of the people’s fairness and prosperity. This concept would become the peasant empowerment base for their prosperity and earnings improvement. Agricultural revitalization is needed to help improve people’s quality of life which could be achieved through: active participation of the society, skills development of human resource, improvement of landholdings title and agricultural productive assets on the basis of farm labor, technology and financial development, enhancement of rural organizations including self-help financial support, and improvement of agriculture resource-based development. IndonesianPenerapan paradigma modernisasi yang mengutamakan prinsip efisiensi dalam pembangunan pertanian menyebabkan terjadinya perubahan struktur sosial masyarakat petani di pedesaan. Perubahan terkait struktur pemilikan lahan pertanian, sehingga terjadi petani lapisan atas dan petani lapisan bawah. 4 dimensi pokok dalam mendefinisikan ”peasant”, yang secara diametral tidak berbeda dan saling menyempurnakan, sehingga perlu kajian perubahan pola hubungan, interaksi, institusi yang dialami oleh masyarakat petani di sepanjang sejarah. Dampak serius pelaksanaan sistem pembangunan terhadap kehidupan petani hendaknya untuk mengkaji kemungkinan dan potensi pemberdayaan petani. Tujuannya agar dapat beradaptasi dan berkelanjutan “tanpa” harus “kehilangan” norma, nilai dan jiwa indigenous knowledge. Ekonomi Kerakyatan merupakan suatu gagasan perekonomian yang mencoba merumuskan dasar interpretasi serta cita-cita pembangunan masyarakat adil dan makmur. Pertimbangan ekonomi kerakyatan dan efisiensi menjadi dasar pemberdayaan petani demi peningkatan pendapatan dan kesejahteraan mereka. Perlu revitalisasi paradigma pembangunan pertanian menjadi peningkatan kualitas hidup dan kesejahteraan petani serta pembangunan pedesaan, melalui: partisipasi aktif sebagai pemberdayaan petani dan masyarakat pedesaan; pengembangan Sumber Daya Manusia (SDM); pemerataan dan peningkatan penguasaan lahan dan asset produktif per tenaga kerja pertanian; teknologi; pembiayaan; pengembangan kelembagaan pertanian-pedesaan dan lembaga keuangan pedesaan yang mandiri, serta pengembangan basis sumberdaya pertanian.